PENGARUH PERGERAKAN HARGA GLOBAL KOMODITAS SEKTOR ENERGI TERHADAP PERGERAKAN HARGA BITCOIN (STUDI KASUS KOMODITAS ENERGI CRUDE OIL DAN NATURAL GAS PERIODE JUNI 2019 - JULI 2022) - Wahyudi, Dendi; Affan Rafi Eko W; Muhammad Sapruwan (Bajang Institute, 2024)
The rapid progress in information technology, particularly in the financial sector involving virtual currencies and continually increasing investment volumes from year to year, serves as motivation for the author to conduct this research. The focus of this study is to analyze the impact of changes in global energy commodity prices, especially Crude Oil and Natural Gas, on the fluctuation of Bitcoin prices. The research method applied is quantitative, using purposive sampling techniques in sample selection. The data source is derived from secondary data taken from the official finance.yahoo.com website with a weekly time series period from June 2019 to July 2022 for each variable under investigation. The analysis results using SPSS22 indicate that the movement of energy commodity prices has a positive and significant influence on changes in Bitcoin prices. Both Crude Oil and Natural Gas, either individually or collectively, contribute positively and significantly to changes in Bitcoin prices. The research findings suggest that the substantial energy consumption in Bitcoin mining activities creates a connection between Bitcoin prices and energy commodity prices. Nevertheless, further research is needed to examine other factors influencing Bitcoin prices.